Pemanfataan Penginderaan Jauh untuk Identifikasi Lahan Potensial Guna Relokasi Perumahan Akibat Bencana Alam: (Studi Kasus : Kecamatan Sutera Kabupaten Pesisir Selatan) - Putri Dwiya Agustin; Fajrin Fajrin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Sutera Subdistrict is an area affected by floods and landslides, causing significant damage to residential areas. Most houses suffered severe damage and are no longer habitable, making housing relocation a crucial post-disaster response. This study aims to identify settlements located in disaster-prone zones and determine potential land areas for housing relocation in Sutera. The method applied involves scoring and weighting combined with spatial analysis of various physical parameters and disaster vulnerability levels.The results indicate that Sutera Subdistrict has considerable potential land for housing relocation, with the highest potential found in Nagari Amping Parak Timur. However, the physical characteristics of the area and variations in disaster vulnerability require selective and planned land utilization. Disaster vulnerability maps serve as an essential basis for spatial planning and development control, particularly in determining relocation sites. In addition, strengthening mitigation efforts and enhancing community preparedness are necessary to minimize disaster risks and support the development of a safer and more sustainable area.